2020
DOI: 10.1093/mnras/staa2954
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of large cavities and disc eccentricity in circumbinary discs

Abstract: We study the mutual evolution of the orbital properties of high mass ratio, circular, co-planar binaries and their surrounding discs, using 3D Smoothed Particle Hydrodynamics simulations. We investigate the evolution of binary and disc eccentricity, cavity structure and the formation of orbiting azimuthal over-dense features in the disc. Even with circular initial conditions, all discs with mass ratios q > 0.05 develop eccentricity. We find that disc eccentricity grows abruptly after a relatively long t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 108 publications
(194 reference statements)
4
62
1
Order By: Relevance
“…Eccentric circumbinary discs are commonly observed in stellar binaries such as GG Tauri A (Guilloteau et al 1999;McCabe et al 2002;Andrews et al 2014;Keppler et al 2020), and are commonly found in numerical simulations (e.g. Miranda et al 2017;MacFadyen & Milosavljević 2008;Ragusa et al 2020) of binaries with mass ratios 𝑞 0.04 (D'Orazio et al 2016;Duffell et al 2020). The eccentric discs can precess coherently (Miranda et al 2017;Ragusa et al 2020), which is consistent with the existence of trapped eccentric modes in circumbinary discs (Muñoz & Lithwick 2020).…”
Section: Disc Morphologysupporting
confidence: 60%
See 2 more Smart Citations
“…Eccentric circumbinary discs are commonly observed in stellar binaries such as GG Tauri A (Guilloteau et al 1999;McCabe et al 2002;Andrews et al 2014;Keppler et al 2020), and are commonly found in numerical simulations (e.g. Miranda et al 2017;MacFadyen & Milosavljević 2008;Ragusa et al 2020) of binaries with mass ratios 𝑞 0.04 (D'Orazio et al 2016;Duffell et al 2020). The eccentric discs can precess coherently (Miranda et al 2017;Ragusa et al 2020), which is consistent with the existence of trapped eccentric modes in circumbinary discs (Muñoz & Lithwick 2020).…”
Section: Disc Morphologysupporting
confidence: 60%
“…This scaling follows from a linear analysis, balancing torques from waves excited at Lindblad resonances with the viscous torque in the disc (Artymowicz & Lubow 1994;Miranda & Lai 2015;Lubow et al 2015), although these anal-yses are commonly found to under-predict cavity sizes when compared with numerical simulations (e.g. MacFadyen & Milosavljević 2008;Ragusa et al 2020), and should be taken at most as a general guideline (Miranda & Lai 2015). Especially at low viscosity, the cavity extends to a larger radius at high Mach number.…”
Section: Binary Orbital Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, numeric simulations have also shown that a companion with a mass ratio q ≥ 0.05 can create an eccentric cavity and trigger an azimuthal clump in the gas (Shi et al 2012;Ragusa et al 2017). For even larger mass ratios, the azimuthal gas contrast may reach a value between two and four in steady state, similar to what is observed in HD 142527 (Price et al 2018;Ragusa et al 2020). Performed with a relatively high turbulent viscosity (α ∼ 5 × 10 −3 ), these simulations did not produce vortices but were still able to trap dust particles in the gas clump, which is rotating at Keplerian velocity.…”
Section: Introductionmentioning
confidence: 58%
“…While not mutually exclusive, another theory suggests that an azimuthal gas pressure maximum can be formed by the interaction between a binary, with a mass ratio q 0.05 with the main star, and the circumbinary disk. Numerical simulations have shown that the massive companion would create a large and eccentric cavity, leading to a gas asymmetry in the gas (Shi et al 2012;D'Orazio et al 2016;Ragusa et al 2017;Price et al 2018) rotating at Keplerian velocity and able to trap dust particles (Calcino et al 2019;Ragusa et al 2020).…”
Section: Vortex Versus Binarymentioning
confidence: 99%